Marketing digital en el incremento de la cartera de clientes, Empresa Friomix en la ciudad de Guayaquil - Suarez Parreño, Cesar Francisco (2024)
A research work was designed that addresses the challenges of the FrioMix company, which with the implementation achieved positive results, focusing on the use of social networks as the main digital marketing strategy for customer acquisition and retention. Information was collected on the current situation of the company, in order to know the competitive environment, and different analyzes were carried out, based on observation, the shortcomings and virtues of the company and the competitors were detected, in the same way an investigation was carried out. descriptive, where the preferences of the company's current and potential clients were discovered through a survey. Considering the time the company has been in the market, innovative tactics such as promotional campaigns and strengthening the online presence are explored. The final objective is to impose the presence of the FrioMix company in the local market by 2024.